Glucose Metabolism in Primary Aldosteronism - Remde, H.; Hanslik, G.; Rayes, N.; Quinkler, M. (Hormone and Metabolic Research, 2015)
In recent years, an increasing number of studies have revealed deleterious effects of aldosterone via the mineralocorticoid receptor (MR). Especially in patients with primary aldosteronism (PA) a significant higher estimated risk of developing cardiovascular comorbidities and comortalities compared to essential hypertensives was reported. As diabetes mellitus and the metabolic syndrome are one of the major contributors to cardiovascular morbidity and mortality their connection to aldosterone excess became a focus of research in PA patients. Several studies assessed the effect of PA on glucose metabolism, the prevalence of diabetes mellitus, and the effect of PA treatment on both revealing different results. Therefore, we performed an extensive literature research. This review focuses on the current knowledge of the connection between aldosterone excess, glucose homeostasis, and diabetes mellitus in patients with PA. We have highlighted this topic from a pro and contra perspective followed by a summarizing concluding remark. Additionally, we have briefly reviewed the data on possible underlying mechanisms and indicated future considerations on the possible impact of cortisol co-secretion in PA.
Keywords: aldosterone; hyperaldosteronism; diabetes mellitus; hypertension; hypokalemia; glucose tolerance